Development of pickled seaweeds (Eucheuma cottonii) - Rosario, Robert I.; De Leon, Sonia Y. (1990.)
ABSTRACT The main objective of the study was to develop a bottled pickled seaweed product that would be deemed as acceptable by consumers. The study consisted of two phases. Phase I aimed to determine the best recipe as well as the best processing method for the product. Phase II aimed to determine the best firming agent as well as its optimum level of use and the length of soaking in this firming agent. The best formulation determined for the product was "Sun Glow Spears" (Levinson, 1965). It was found that the best processing method for bottled pickled seaweeds was to simmer the seaweed with the pickling solution at 62.78° then immediately transfer them to a bottle and seal immediately. The presence of sulfate groups in the chemical structure of the seaweed necessitated the addition of 1% potassium citrate to the pickling solution to avoid a possible hydrolysis of the product. The use of 0.7% potassium hydroxide as firming agent was found to be the most suitable for the bottled pickled seaweed product. The optimum length of soaking, on the other hand, was found to be three hours. The general acceptability of the final product measured by the 9-point hedonic rating scale was found to be "moderately acceptable".
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Marine algae